Editorial: Role of Non-Coding RNAs in Animals - Duy Ngoc Do; Prashanth Suravajhala (Animals, 2023)
The importance of non-coding RNAs (ncRNAs), such as microRNAs (miRNA), long non-coding RNAs (lncRNA), and circular RNAs (circRNA), in gene regulation is increasingly being appreciated in many species [...]